Analisis Profile Metakognisi Siswa Dalam Pemecahan Masalah Pada Pembelajaran Matematika Kelas VIII Semester Ganjil SMP Negeri 3 Sawit - RAHAYU UTAMI, DWI; , Masduki, S.Si, M.Si (2017)
This study aimed to describe the profile of metacognition students who have math skills of high, medium and low in solving story relations and functions with indicators of problem solving is at the stage of understanding, planning, implementation and examination of students who have the math skills of high, medium and low in solving problems in the story about the A class VIII SMP Negeri 3 Sawit. This research is a qualitative descriptive. Subjects of this study is 6 students drawn from class VIII A of SMP Negeri 3 Sawit. The data collection technique using the test method, interviews, observation and documentation. The validity of the data using triangulation techniques and resources. Data analysis techniques carried out in three stages: data reduction, exposure data, and conclusions or verification. The results showed that students who have high math skills gained roughly 25% of the indicators meet metacognitive skills in the stage of understanding, planning, implementation and inspection. Students who have math skills are getting a percentage 46.875% does not fully comply indicators skills of metacognition in the planning, execution and examination, while students who have math skills lower gain percentage of 28.125% not meet indicators skills of metacognition in the stage of understanding, planning, execution and inspection in in solving the problem.